2021
DOI: 10.1093/ibd/izab122
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Deep Learning to Analyze Whole Slide Images of Colonic Biopsies for Associations Between Eosinophil Density and Clinicopathologic Features in Active Ulcerative Colitis

Abstract: Background Eosinophils have been implicated in the pathogenesis of ulcerative colitis and have been associated with disease course and therapeutic response. However, associations between eosinophil density, histologic activity, and clinical features have not been rigorously studied. Methods A deep learning algorithm was trained to identify eosinophils in colonic biopsies and validated against pathologists’ interpretations. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Furthermore, basal plasmacytosis is seen only in a minority of cases of relapse and thus is a relatively insensitive marker [ 15 ].⁠ Concerning point (c), there is only limited data on the association between eosinophils and relapse. Recently, Vande Casteele et al [ 16 ]⁠ quantified eosinophils in colonic biopsies and found correlations between eosinophil density and both disease extent and corticosteroid therapy, but crucially not with histologic activity. These factors confirm our belief that neutrophils are the only real marker of activity in IBD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, basal plasmacytosis is seen only in a minority of cases of relapse and thus is a relatively insensitive marker [ 15 ].⁠ Concerning point (c), there is only limited data on the association between eosinophils and relapse. Recently, Vande Casteele et al [ 16 ]⁠ quantified eosinophils in colonic biopsies and found correlations between eosinophil density and both disease extent and corticosteroid therapy, but crucially not with histologic activity. These factors confirm our belief that neutrophils are the only real marker of activity in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Because basal plasmacytosis is known to have high predictive value for the first diagnosis of IBD [ 7 , 8 , 11 , 12 ]⁠ and for the differential diagnosis with other forms of colitis [ 13 ],⁠ it has been hypothesized that an absence of basal plasmacytosis is required in healed IBD [ 14 ].⁠ This is contradictory, because the presence of basal plasma cells in this phase of disease is a sign of pre-existing IBD, and the number of plasma cells needed to document this feature is not known. Eosinophils, intermingled with plasma cells, are present at variable frequency in active and quiescent IBD [ 15 , 16 ].⁠ Therefore, the presence of eosinophils does not rule out inactive disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first pioneering application of AI to histology in UC came from Vande Casteele et al (46) who trained a deep learning algorithm to quantify eosinophils in colonic biopsies. This AI model proved a high agreement with manual eosinophil count performed by human pathologists (ICC = 0.81-0.92) in a cohort of 88 UC patients with histologically active disease (46). Although no correlation between AI eosinophil count and histological activity was found, this work paved the way for other studies in the field.…”
Section: Ai For Histologymentioning
confidence: 99%
“…It creates opportunities for exploring the relationships among features and building highly efficient models. Automated image recognition using deep learning methods also has been applied in the endoscopic images and pathological images recognition of IBD ( 21 , 26 28 ). Moreover, in search of new well-performing markers at the gene and microbiome level, the ML methods showed the greatest contribution in variables screening ( 29 , 30 ).…”
Section: Introductionmentioning
confidence: 99%